The poetics of veiling in the poetry of Al-Sharif Al-Radi - حيدر محسن; رباح علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Poetic language is a suggestive language, especially since this language carries in its harmonious details special connotations that differ from one poetic purpose to another, and from one creator to another. This requires a distinct language for each content. Religious contents require special terminology, as we find in the term “veiling,” which refers to curtains and their unveiling. To reach true knowledge. Al-Sharif Al-Radi is a poet distinguished by his belonging to an ancient Muslim family, and he diversified his poetic purposes. The poetry of veiling had a special color in each purpose, different from the other purposes. We find that spinning has a Sufi philosophy, Which made him seek to remove the veils that separated him from her, so he passionately sought to remove them, and lamentation was a purpose full of veils in his poetry, but they are religious veils that lead to permanent survival, and are not based on the merits of a dead person. His elegies were double veils. In the description, the imaginary representations seemed to be based on veils and their role in deepening the poetics that reveal purity, social and religious censorship, authoritarianism, and others. The poems were filled with poetic concepts loaded with concepts, such as religious concepts, such as (light), and concepts of power, such as (greeds), (despair), and others that reveal the restrictions in society. Obscuration and backbiting intertwined, forming an absolute emotional unity represented by the revelation of a special vision in religion, authority, and society, a vision whose tools were used to reveal the inadequacy of the mind and its limitations in the face of knowledge of divine truths.